Perkembangan Peradaban Islam Indonesia Pada Masa Reformasi - Muhammad Auliya Elhakim; Agung Hidayatul Irsyad; Nasikhin; Fihris (KAMALIYAH : Jurnal Pendidikan Agama Islam, 2023)
This qualitative library research explores the role of Islamic civilization in Indonesia during the reformation era. It delves into Indonesia's historical narrative, emphasizing nationalism post-independence. Islam's roots trace back to the 7th century, flourishing in the 13th century. Despite rapid growth since independence, Islam hasn't been declared the nation's official ideology, favoring Pancasila for its pluralistic ethos. Post-reform, Islam's influence is significant, yet diverse Islamic movements emerged, some advocating for Islamic law. These dynamics create sensitivity around Islam, challenging its development amidst issues like representation, blasphemy, and the intersection of religion and politics. Consolidation and alignment of Islamic interests are essential for navigating this complex landscape.